2011
DOI: 10.1002/bdd.760
|View full text |Cite
|
Sign up to set email alerts
|

Are there differences in the catalytic activity per unit enzyme of recombinantly expressed and human liver microsomal cytochrome P450 2C9? A systematic investigation into inter‐system extrapolation factors

Abstract: The 'relative activity factor' (RAF) compares the activity per unit of microsomal protein in recombinantly expressed cytochrome P450 enzymes (rhCYP) and human liver without separating the potential sources of variation (i.e. abundance of enzyme per mg of protein or variation of activity per unit enzyme). The dimensionless 'inter-system extrapolation factor' (ISEF) dissects differences in activity from those in CYP abundance. Detailed protocols for the determination of this scalar, which is used in population i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 44 publications
2
24
0
Order By: Relevance
“…For example, for CYP1A2, Venkatakrishnan and colleagues reported a 4-fold difference in the RAF when comparing methoxyresorufin or phenacetin (Lipscomb & Poet, 2008;Venkatakrishnan et al, 2000). The same phenomenon was identified for CYP2C9 using diclofenac, tolbutamine and Swarfarin (Crewe et al, 2011;Kumar et al, 2006;Locuson et al, 2007) and with CYP3A4, a 2-fold difference between nifedipine and testosterone (Emoto & Iwasaki, 2007;Patki et al, 2003) is evident. In our study, a 5-fold difference was observed (RAF of 9.8 for testosterone and 49 for nifedipine).…”
Section: Discussionsupporting
confidence: 67%
“…For example, for CYP1A2, Venkatakrishnan and colleagues reported a 4-fold difference in the RAF when comparing methoxyresorufin or phenacetin (Lipscomb & Poet, 2008;Venkatakrishnan et al, 2000). The same phenomenon was identified for CYP2C9 using diclofenac, tolbutamine and Swarfarin (Crewe et al, 2011;Kumar et al, 2006;Locuson et al, 2007) and with CYP3A4, a 2-fold difference between nifedipine and testosterone (Emoto & Iwasaki, 2007;Patki et al, 2003) is evident. In our study, a 5-fold difference was observed (RAF of 9.8 for testosterone and 49 for nifedipine).…”
Section: Discussionsupporting
confidence: 67%
“…Alternatively, abundance may not reflect the activity when various CYP2C9 genotypes are assessed together. In addition, differences in expression of cytochrome b5 and NADPH P450 reductase in different individuals have been reported to lead to disparities in CYP2C9 enzyme activity (Crewe et al, 2011). These were not known for individual samples under study.…”
Section: Discussionmentioning
confidence: 99%
“…41 Because the in vitro enzyme kinetic data used relative activity to express CYP-mediated NAPQI formation, 44 both in vitro and in vivo values and systemic information was combined to convert this unit to the absolute amount of NAPQI. The unbound intrinsic clearance (CL u,int(enzyme) ) of each CYP and UGT enzyme and the total intrinsic clearance of sulfotransferases were normalized to pmol enzyme (CYPs) or microsomal protein (UGTs and total sulfotransferases) levels by incorporating system-specific information including enzyme abundance, microsomal protein expression level, liver weight, intersystem extrapolation factor for scaling of recombinant CYP in vitro kinetic data, 48 which are provided by the ADME simulator, and intrinsic clearance derived from in vivo study. The maximum velocity for each phase I and phase II pathway or enzymes (V max(enzyme) ) was derived from the calculated CL u,int(enzyme) values using the following equation:…”
Section: Methodsmentioning
confidence: 99%